2022
DOI: 10.3389/fpls.2022.921074
|View full text |Cite
|
Sign up to set email alerts
|

Blocked at the Stomatal Gate, a Key Step of Wheat Stb16q-Mediated Resistance to Zymoseptoria tritici

Abstract: Septoria tritici blotch (STB), caused by the fungus Zymoseptoria tritici, is among the most threatening wheat diseases in Europe. Genetic resistance remains one of the main environmentally sustainable strategies to efficiently control STB. However, the molecular and physiological mechanisms underlying resistance are still unknown, limiting the implementation of knowledge-driven management strategies. Among the 22 known major resistance genes (Stb), the recently cloned Stb16q gene encodes a cysteine-rich recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 68 publications
5
30
0
Order By: Relevance
“…This finding was confirmed by measuring the pore width and g s of the treated leaves over time ( Figure 1 ). This outcome was consistent with a recent study that found Stb16q mediates an early and temporary stomatal closure in response to an avirulent Z. tritici isolate ( Battache et al., 2022 ). Typically, each stomatal pore is surrounded by two guard cells, that are extremely specialized in structure and function, and variations in the turgor pressure of these cells regulate the pore aperture size.…”
Section: Discussionsupporting
confidence: 93%
“…This finding was confirmed by measuring the pore width and g s of the treated leaves over time ( Figure 1 ). This outcome was consistent with a recent study that found Stb16q mediates an early and temporary stomatal closure in response to an avirulent Z. tritici isolate ( Battache et al., 2022 ). Typically, each stomatal pore is surrounded by two guard cells, that are extremely specialized in structure and function, and variations in the turgor pressure of these cells regulate the pore aperture size.…”
Section: Discussionsupporting
confidence: 93%
“…For example, Z . tritici strains harbouring the avirulence genes AvrStb16q and AvrStb6 were also shown to be mostly arrested at the stomatal penetration step on Stb16q and Stb6 wheat cultivars, respectively (Battache et al ., 2022). This suggests that the stomatal penetration step is key to mediating various forms of disease resistance to Zymoseptoria species.…”
Section: Figmentioning
confidence: 99%
“…This correlates with reduced levels of subsequent disease. Changes in stomatal aperture (transient closure) in resistant wheat cultivars following contact with avirulent fungal hyphae may be a key feature (Battache et al ., 2022). Overall, many of these characteristics are somewhat more reminiscent of events typical of PAMP/MAMP‐triggered plant immunity (Zhang et al ., 2008).…”
Section: Figmentioning
confidence: 99%
“…Z. tritici is apoplastic with a biphasic infection process (Petit-Houdenot et al, 2021). After penetration into wheat leaves through stomata, the fungus colonizes the apoplast for 8-11 days while the host remains symptomless (Battache et al, 2022). This long asymptomatic phase is .…”
Section: Introductionmentioning
confidence: 99%
“…Z. tritici is apoplastic with a biphasic infection process (Petit-Houdenot et al ., 2021). After penetration into wheat leaves through stomata, the fungus colonizes the apoplast for 8-11 days while the host remains symptomless (Battache et al ., 2022). This long asymptomatic phase is followed by a rapid onset of necrotic symptoms, associated with the development of fungal asexual fruiting bodies called pycnidia, which contain the pycnidiospores that further spread the disease (Sánchez-Vallet et al ., 2015).…”
Section: Introductionmentioning
confidence: 99%